The impact of the Katina model on developing the skills of preparing theatrical texts based on folk tales for students of the Institute of Fine Arts in the school theater subject (Journal of the College of Basic Education, 2023)
Summary of the research:The current research aims to develop the skills of preparing theatrical texts based on folk tales for the students of the Institute of Fine Arts in the school theater subject according to the Katina model, and then measuring the size of the effect in developing the skills of preparing texts. Before and after, where the research community consisted of (30) male and female students from the theater department at the Institute of Fine Arts, second stage / Karkh. The researcher prepared two tools for the current research:First: a knowledge test consisting of two questionsSecond: skill test (observation form)Among the most important results of the current research:1. The effect size of the program in the post-cognitive test was (0.45), and for this reason, the effect size is highly effective for the experimental group.2. The effect size of the program in the post-skills performance test was (0.21). Therefore, the effect size is considered to have a high impact for the experimental group.Conclusions:1. The clarity of the program paragraphs had a direct positive impact, which contributed to increasing the attention process and directing towards the specified goal.2. Clearly increasing the skills of preparing theatrical texts for the experimental group itself gives a clear indication of the effectiveness of the educational program.Recommendations:1. Inclusion of topics and skills related to the preparation and practice of theatrical texts by students of the Institute of Fine Arts within the school theater course2. The possibility of benefiting from the Katina model to develop the skills of preparing theatrical texts for students in teaching some practical skills in generalKeywords: Katina model, text preparation, school theatre.School theater subject